Prescribing Pattern of Ampicillin and Cloxacillin: Sensitivity and Responsiveness in Pneumonia: Antibiotic resistance - Haleema Shah; Uzma Bibi; Zul Kamal; Muhammad Esa; Muhammad Naeem; Saleh Ahmad; Muhammad Shafique (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Antimicrobial resistance (AMR) is now a global pandemic and a future threat to the existence of many clinical antibiotics. The excessive overuse in fisheries, poultries, and dairy farms and its irrational prescribing practices are the key factors that lead us to AMR explosions. The current main research objective is to evaluate the empirical practices of ampicillin along with cloxacillin, which are one of the running antibiotics in clinical practices, in most of the tertiary care hospitals in Khyber Pakhtunkhwa, Pakistan. In this study, the prescribing attitude, sensitivity and responsiveness of these two combinatory antibiotics (ampicillin-cloxacillin) in pediatric/adult pneumonia patients were evaluated in one of the public sector tertiary care hospitals in Mardan. Retrospective data was collected from pediatric ward A and medical A ward (adult), among which a total of n= 90 patient’s prescriptions were evaluated for prescribing practices, WHO core indicators, polypharmacy as well as responsiveness and sensitivity of ampicillin and cloxacillin from hospital longevity. The ampicillin responsiveness was sorted out among all those patients that stayed for a long time in the hospital, and during which the antibiotic therapies were switched from time to time. A total of n= 90 pneumonia patients (40 % & 60 % female) cases were evaluated for ampicillin/cloxacillin (combination) hospital stay longevity and responsiveness. 46 % of patients were under the age of 1–20 years, whereas 31 % were adults between the age of 61–80 years. WHO indicators revealed, that in the prescribed medications (n=918 drugs total, among n=90 patients) 22.33 % of antibiotics were prescribed, where 31.37 % consisted of injectables. Among the antibiotics classes, 17 % of pneumonia patients received penicillin, among which 26.25 % were ampicillin + cloxacillin in the prescribing practices. Ampicillin + cloxacillin responsiveness in pneumonia patients was recorded from the hospital stay and longevity (days) of the patients during their empirical therapy. 46.98 % of pneumonia patients recovered within three days, whereas 40.96 % of patients recovered within six days with ampicillin + cloxacillin (combination therapy). While 10.84 % were stabilized within nine days, though, some patients (1.20 %), recovered after 12 days with ampicillin/cloxacillin (combination therapy). Thus, it may be concluded from the current studies, that the decrease in responsiveness to ampicillin/cloxacillin (combination therapy) and the increase in the hospital longevity of patients, may be an indication of antimicrobial resistance (AMR) in pneumonia patients. Though the studies are limited to a very specific number of patients, as well as only to the hospital longevity (stay) parameters of the patients in a tertiary care hospital. These studies should be subjected further to more extensive vigilant research.